Ethnobotanical study of medicinal plants used in the treatment of high blood pressure in the region of Tlemcen (Northwestern Algeria) - Sara Hassaïne (Journal of Pharmacy & Pharmacognosy Research, 2019)
Context: Ethnobotanical study of medicinal plants used in the treatment of high blood pressure in the region of Tlemcen (Northwestern Algeria).